Preparation method of polyester
The melt-condensation polymerization of bis-(5-carboxyfuryl) ether and diol into polyester is solved, and the problem of insufficient toughness of bio-based polyester is achieved, taking into account both heat resistance and toughness, and the production process is simplified.
Patent Information
- Application Number
- CN202510059418.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-03-25
AI Technical Summary
The application of bio-based polyethylene 2,5-furandicarboxylate (PEF) in films, bottles and other fields is limited by the problem of poor toughness, and existing modification methods will lead to a decrease in heat resistance when improving toughness.
Bis-(5-carboxyfuryl) ether or its esterides are used as monomers and polymerized with diols to form polyester by melt-condensation. The bisfuran ring is used to maintain the rigidity of the chain segment, and the ether bonds are combined to improve flexibility, thereby improving toughness.
While ensuring the heat resistance of polyester, it significantly improves its toughness. It is suitable for films, bottles and other fields, and simplifies the production process, improves the utilization rate of equipment, and avoids the use of a large number of organic solvents.
Smart Images

Figure CN119684583A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of organic synthesis, and in particular to a method for preparing polyester. Background Art
[0002] Bio-based polyethylene 2,5-furandicarboxylate (PEF) has attracted widespread attention due to its excellent heat resistance, but its poor toughness limits its application in films, bottle flakes and other fields.
[0003] In the prior art, research on toughening modification of PEF mainly focuses on introducing a third monomer into the PEF copolymer, such as introducing aliphatic or alicyclic structures with better flexibility. Although this method increases the flexibility of the polyester chain segment, it leads to a decrease in the heat resistance of the polyester.
[0004] Therefore, how to ensure the heat resistance of polyester while improving its toughness has become an urgent problem to be solved. Summary of the invention
[0005] In order to solve the above-mentioned technical problems, the present application provides a method for preparing polyester, which is obtained by melt polycondensation of bis-(5-carboxyfurfuryl) ether or its esterification product as a monomer with a diol.
[0006] The structural formula of the polyester is shown below:
[0007]
[0008] Here, n is an integer of 20 to 100, and R represents a structural unit of an aliphatic or alicyclic diol.
[0009] By adopting the above technical scheme, the polyester is synthesized by melt polycondensation using bis-(5-carboxyfurfuryl) ether monomers from bio-based sources. The structure of the bisfuran ring in bis-(5-carboxyfurfuryl) ether can maintain the rigidity of the chain segment and ensure the good heat resistance of the polyester. At the same time, the presence of the ether bond can improve the flexibility of the polyester and increase its toughness. Therefore, the polyester prepared using bis-(5-carboxyfurfuryl) ether or its esterification product as a monomer can not only ensure the heat resistance of the polyester, but also improve its toughness.
[0010] Preferably, the preparation method uses bis-(5-carboxyfurfuryl) ether or its esterified product as a monomer, and performs melt polycondensation with a diol in the presence of an esterification or transesterification catalyst, a polycondensation catalyst and a stabilizer to obtain the product.
[0011] Preferably, the preparation method uses bis-(5-carboxyfurfuryl) ether or its ester as a monomer, reacts with a diol in the presence of an esterification or transesterification catalyst to obtain an intermediate product, and then the intermediate product reacts with the polycondensation catalyst and the stabilizer to obtain the intermediate product.
[0012] Preferably, the molar ratio of the bis-(5-carboxyfurfuryl) ether or its ester to the diol is 1:(1.2-3.0).
[0013] Preferably, the molar ratio of the esterification or transesterification catalyst to the bis-(5-carboxyfurfuryl) ether or its esterified product is (0.3-3.0):1000.
[0014] Preferably, the molar ratio of the polycondensation catalyst to the bis-(5-carboxyfurfuryl) ether or its ester is (0.3-3.0):1000.
[0015] Preferably, the molar ratio of the stabilizer to the bis-(5-carboxyfurfuryl) ether or its ester is (0.4-3.0):1000.
[0016] Preferably, bis-(5-carboxyfurfuryl) ether or its esterified product is used as a monomer, and in the presence of an esterification or transesterification catalyst, reacted with a diol at 150 to 240° C. for 2.0 to 8.0 hours to obtain an intermediate product, and the intermediate product is reacted with the polycondensation catalyst and the stabilizer at 170 to 290° C. and a vacuum degree of ≤200 Pa for 1.5 to 10 hours to obtain a polyester;
[0017] Preferably, the intermediate product is reacted with the polycondensation catalyst and the stabilizer at 220 to 290° C. and a vacuum degree of ≤200 Pa for 1.5 to 10 hours to obtain polyester.
[0018] In some embodiments, the vacuum degree can be 10Pa, 20Pa, 30Pa, 40Pa, 50Pa, 60Pa, 70Pa, 80Pa, 90Pa, 100Pa, 110Pa, 120Pa, 130Pa, 140Pa, 150Pa, 160Pa, 170Pa, 180Pa, 190Pa, 200Pa and is not limited thereto.
[0019] Preferably, the diol is selected from one or more of ethylene glycol, butanediol, hexanediol, neopentyl glycol, a cis-trans ratio mixture of cyclohexanedimethanol, tricyclodecane dimethanol, dicyclopentanediol, 1,5-dimethyldicyclopentanediol, and pentacyclopentadecanediol;
[0020] Preferably, the cyclohexanedimethanol is selected from one or more of 1,4-cyclohexanedimethanol cis-trans mixture, 1,2-cyclohexanedimethanol, and 1,3-cyclohexanedimethanol;
[0021] Preferably, the cis-trans ratio of the 1,4-cyclohexanedimethanol cis-trans mixture is 0.25-4.0.
[0022] Preferably, the esterification or transesterification catalyst is selected from one or more of zinc acetate, tetrabutyl titanate, isopropyl titanate, titanium dioxide, dibutyltin oxide, stannous isooctanoate, and monobutyltin triisooctanoate;
[0023] Preferably, the polycondensation catalyst is selected from one or more of antimony trioxide, antimony acetate, titanium dioxide, dibutyltin oxide, stannous isooctanoate, monobutyltin triisooctanoate, and germanium dioxide;
[0024] Preferably, the stabilizer is a phosphorus stabilizer;
[0025] Preferably, the phosphorus stabilizer is selected from one or more of phosphorous acid, hypophosphorous acid, pyrophosphoric acid, ammonium phosphate, trimethyl phosphate, dimethyl phosphate, triphenyl phosphate, diphenyl phosphate, triphenyl phosphite, diphenyl phosphite, ammonium phosphite, and diammonium dihydrogen phosphate.
[0026] By adopting the above technical scheme, the preparation method of the present application optimizes the catalyst ratio and performs gradient temperature increase during the polymerization process to achieve melt polycondensation to prepare polyester. The production process of melt polycondensation is simple, the equipment utilization rate is high, and the use of a large amount of organic solvents is avoided, which can save complex processes such as solvent recovery and treatment.
[0027] In summary, this application has the following beneficial effects:
[0028] 1. The preparation method provided in the present application uses bis-(5-carboxyfurfuryl) ether monomers from bio-based sources to synthesize polyesters through melt polycondensation. The structure of the bisfuran ring in bis-(5-carboxyfurfuryl) ether can maintain the rigidity of the chain segment and ensure the good heat resistance of the polyester. At the same time, the presence of the ether bond can improve the flexibility of the polyester and increase its toughness. Therefore, the polyester prepared using bis-(5-carboxyfurfuryl) ether or its esterification product as a monomer can not only ensure the heat resistance of the polyester, but also improve its toughness.
[0029] 2. The present application provides a method for preparing polyester by melt polycondensation, which has a simple production process, high equipment utilization rate, avoids the use of large amounts of organic solvents, and can omit complex processes such as solvent recovery and treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0031] Figure 1 It is the polybis-(5-carboxyfurfuryl) ether butanediol ester prepared in Example 1 of the present application1 H-NMR spectrum;
[0032] Figure 2 It is the polybis-(5-carboxyfurfuryl) ether butanediol ester prepared in Example 1 of the present application 13 C-NMR spectrum. DETAILED DESCRIPTION
[0033] Example
[0034] The following examples are methods for preparing the polyester of the present application.
[0035] The general structural formula of the polyesters of the following examples is as follows:
[0036]
[0037] Wherein, n is an integer of 20-100, and R represents a structural unit of an aliphatic or alicyclic diol.
[0038] Example 1
[0039] Add bis-(5-carboxyfurfuryl) ether and ethylene glycol into the reactor at a molar ratio of 1:1.6, then add dibutyltin oxide, a catalyst with a molar amount of 1‰ of bis-(5-carboxyfurfuryl) ether, and gradually heat to 160°C for esterification under the protection of high-purity nitrogen. React for 6.0 hours, then add 1.0‰ of bis-(5-carboxyfurfuryl) ether as a polycondensation catalyst, antimony acetate, and 1.0‰ of triphenyl phosphate, a stabilizer, and gradually heat to 210°C. The vacuum degree is gradually reduced to 30Pa, and the reaction is carried out for 7.0 hours to obtain polybis-(5-carboxyfurfuryl) ether ethylene glycol ester. The obtained polyester was tested for its intrinsic viscosity and thermal stability. The intrinsic viscosity of the polyester is 0.97dL / g, the glass transition temperature is 72°C, and the thermal weight loss temperature (T d ,5%) is 336℃ and the elongation at break is 210±11%.
[0040] Example 2
[0041] Add bis-(5-carboxyfurfuryl) ether and 1,4-butanediol into the reactor at a molar ratio of 1:1.8, then add zinc acetate as a catalyst with a molar amount of 0.3‰ of bis-(5-carboxyfurfuryl) ether, and gradually heat to 160°C for esterification under the protection of high-purity nitrogen. React for 3.0 hours, then add antimony acetate as a polycondensation catalyst with a molar amount of 1.0‰ of bis-(5-carboxyfurfuryl) ether, 2.0‰ of phosphorous acid as a stabilizer, gradually heat to 210°C, gradually reduce the vacuum degree to 30Pa, react for 7.0 hours, and obtain polybis-(5-carboxyfurfuryl) ether butanediol ester. The obtained polyester was tested for its intrinsic viscosity and thermal stability. The intrinsic viscosity of the polyester is 0.86dL / g, the glass transition temperature is 22.3°C, and the thermal weight loss temperature (T d,5%) is 338℃ and the elongation at break is 460±18%.
[0042] Example 3
[0043] Add bis-(5-carboxyfurfuryl) ether and 1,6-hexanediol into the reactor in a molar ratio of 1:1.2, then add tetrabutyl titanate, a catalyst with a molar amount of 1.5‰ of bis-(5-carboxyfurfuryl) ether, and gradually heat to 160°C for esterification under the protection of high-purity nitrogen. React for 5.0 hours, then add 0.3‰ of bis-(5-carboxyfurfuryl) ether, a condensation catalyst antimony trioxide, and 0.4‰ of a stabilizer hypophosphorous acid, and gradually heat to 210°C. The vacuum degree is gradually reduced to 100Pa, and the reaction is carried out for 4 hours to obtain polybis-(5-carboxyfurfuryl) ether hexanediol ester. The obtained polyester was tested for its intrinsic viscosity and thermal stability. The intrinsic viscosity of the polyester is 1.19dL / g, the glass transition temperature is 15.1°C, and the thermal weight loss temperature (T d ,5%) is 347℃ and the elongation at break is 530±37%.
[0044] Example 4
[0045] Add bis-(5-carboxyfurfuryl) ether and neopentyl glycol into the reactor in a molar ratio of 1:3.0, then add 3‰ of bis-(5-carboxyfurfuryl) ether as catalyst titanium dioxide, under the protection of high-purity nitrogen, gradually heat up to 150°C for esterification, react for 8.0h, then add 3.0‰ of bis-(5-carboxyfurfuryl) ether as polycondensation catalyst dibutyltin oxide, 3.0‰ of stabilizer ammonium phosphate, gradually heat up to 220°C, gradually reduce the vacuum degree to 10Pa, react for 10.0h, and obtain polybis-(5-carboxyfurfuryl) ether neopentyl glycol ester. The obtained polyester was tested for intrinsic viscosity, thermal stability, etc. The intrinsic viscosity of the polyester was 0.95dL / g, the glass transition temperature was 47.2℃, and the thermal weight loss temperature (T d ,5%) is 376℃ and the elongation at break is 190±27%.
[0046] Example 5
[0047] Bis-(5-carboxyfurfuryl) ether and tricyclodecane dimethanol were added to the reactor in a molar ratio of 1:2, and then 1‰ of the catalyst stannous isooctanoate of the bis-(5-carboxyfurfuryl) ether was added. Under the protection of high-purity nitrogen, the temperature was gradually raised to 180°C for esterification and the reaction was carried out for 6.0 hours. Then, 1.0‰ of the condensation catalyst stannous isooctanoate of the bis-(5-carboxyfurfuryl) ether and 1.0‰ of the stabilizer trimethyl phosphate were added, and the temperature was gradually raised to 230°C. The vacuum degree was gradually reduced to 30Pa, and the reaction was carried out for 7.0 hours to obtain polybis-(5-carboxyfurfuryl) ether tricyclodecane dimethanol ester. The obtained polyester was tested for characteristic viscosity, thermal stability, etc. The characteristic viscosity of the polyester was 0.79dL / g, the glass transition temperature was 85°C, and the thermal weight loss temperature (T d ,5%) is 392℃ and the elongation at break is 260±22%.
[0048] Example 6
[0049] Add bis-(5-carboxyfurfuryl) ether and dicyclopentanediol into the reactor in a molar ratio of 1:1.6, then add dibutyltin oxide, a catalyst with a molar amount of 0.3‰ of bis-(5-carboxyfurfuryl) ether, and gradually heat to 170°C for esterification under the protection of high-purity nitrogen. React for 6.0 hours, then add 1.0‰ of bis-(5-carboxyfurfuryl) ether, a polycondensation catalyst, germanium dioxide, and 1.0‰ of diphenyl phosphate, a stabilizer, and gradually heat to 220°C. The vacuum degree is gradually reduced to 30Pa, and the reaction is carried out for 7.0 hours to obtain polybis-(5-carboxyfurfuryl) ether dicyclopentanediol ester. The obtained polyester is tested for its intrinsic viscosity and thermal stability. The intrinsic viscosity of the polyester is 0.70dL / g, the glass transition temperature is 79°C, and the thermal weight loss temperature (T d ,5%) is 374℃ and the elongation at break is 190±14%.
[0050] Example 7
[0051] Bis-(5-carboxyfurfuryl) ether and 1,5-dimethyldicyclopentanediol were added to the reactor in a molar ratio of 1:1.6, and then a catalyst dibutyltin oxide with a molar amount of 1‰ of bi-(5-carboxyfurfuryl) ether was added. Under the protection of high-purity nitrogen, the temperature was gradually raised to 190°C for esterification and the reaction was carried out for 6.0 hours. Then, a polycondensation catalyst antimony acetate with a molar amount of 1.0‰ of bi-(5-carboxyfurfuryl) ether and a stabilizer triphenyl phosphite with a molar amount of 1.0‰ were added, and the temperature was gradually raised to 230°C. The vacuum degree was gradually reduced to 30Pa, and the reaction was carried out for 7.0 hours to obtain poly-bis-(5-carboxyfurfuryl) ether 1,5-dimethyldicyclopentanediol ester. The obtained polyester was tested for intrinsic viscosity, thermal stability, etc. The intrinsic viscosity of the polyester was 0.68dL / g, the glass transition temperature was 81°C, and the thermal weight loss temperature (T d,5%) is 377℃ and the elongation at break is 160±26%.
[0052] Example 8
[0053] Bis-(5-carboxyfurfuryl) ether and pentacyclopentadecanediol were added to the reactor in a molar ratio of 1:2.5, and then 0.8‰ of bis-(5-carboxyfurfuryl) ether was added as a catalyst zinc acetate. Under the protection of high-purity nitrogen, the temperature was gradually raised to 190°C for esterification and the reaction was continued for 6.0 hours. Then 0.8‰ of bis-(5-carboxyfurfuryl) ether was added as a polycondensation catalyst antimony acetate and 1.0‰ of a stabilizer diphenyl phosphite. The temperature was gradually raised to 240°C, and the vacuum degree was gradually reduced to 30Pa. The reaction was continued for 7.0 hours to obtain polybis-(5-carboxyfurfuryl) ether pentacyclopentadecanediol ester. The obtained polyester was tested for its intrinsic viscosity and thermal stability. The intrinsic viscosity of the polyester was 0.78dL / g, the glass transition temperature was 83°C, and the thermal weight loss temperature (T d ,5%) is 377℃ and the elongation at break is 240±22%.
[0054] Example 9
[0055] Bis-(5-carboxyfurfuryl) ether and 1,2-cyclohexanedimethanol were added to the reactor in a molar ratio of 1:1.6, and then a catalyst dibutyltin oxide with a molar amount of 1‰ of bis-(5-carboxyfurfuryl) ether was added. Under the protection of high-purity nitrogen, the temperature was gradually raised to 180°C for esterification and the reaction was carried out for 6.0 hours. Then, a polycondensation catalyst antimony acetate with a molar amount of 1.0‰ of bis-(5-carboxyfurfuryl) ether and a stabilizer ammonium phosphite with a molar amount of 1.0‰ were added, and the temperature was gradually raised to 230°C. The vacuum degree was gradually reduced to 30Pa, and the reaction was carried out for 7.0 hours to obtain polybis-(5-carboxyfurfuryl) ether 1,2-cyclohexanedimethanol ester. The obtained polyester was tested for intrinsic viscosity, thermal stability, etc. The intrinsic viscosity of the polyester was 0.52dL / g, the glass transition temperature was 49°C, and the thermal weight loss temperature (T d ,5%) is 353℃ and the elongation at break is 19±3%.
[0056] Example 10
[0057] Bis-(5-carboxyfurfuryl) ether and 1,3-cyclohexanedimethanol were added to the reactor in a molar ratio of 1:1.6, and then a catalyst dibutyltin oxide with a molar amount of 1‰ of bis-(5-carboxyfurfuryl) ether was added. Under the protection of high-purity nitrogen, the temperature was gradually raised to 190°C for esterification and the reaction was carried out for 6.0 hours. Then, a polycondensation catalyst antimony acetate with a molar amount of 1.0‰ of bis-(5-carboxyfurfuryl) ether and a stabilizer diammonium dihydrogen phosphate with a molar amount of 1.0‰ were added, and the temperature was gradually raised to 220°C. The vacuum degree was gradually reduced to 30Pa, and the reaction was carried out for 7.0 hours to obtain polybis-(5-carboxyfurfuryl) ether 1,3-cyclohexanedimethanol ester. The obtained polyester was tested for intrinsic viscosity, thermal stability, etc. The intrinsic viscosity of the polyester was 0.60dL / g, the glass transition temperature was 50°C, and the thermal weight loss temperature (T d ,5%) is 361℃ and the elongation at break is 27±9%.
[0058] Embodiment 11
[0059] Bis-(5-carboxyfurfuryl) ether and 1,4-cyclohexanedimethanol were added to the reactor in a molar ratio of 1:1.6, wherein the ratio of cis-trans isomers of 1,4-cyclohexanedimethanol was 0.25, and then 1‰ of dibutyltin oxide catalyst was added to the di-(5-carboxyfurfuryl) ether. Under the protection of high-purity nitrogen, the temperature was gradually raised to 190°C for esterification and the reaction was continued for 6.0h. Then, 1.0‰ of antimony acetate, a polycondensation catalyst, and 1.0‰ of triphenyl phosphate, a stabilizer, were added to the di-(5-carboxyfurfuryl) ether. The temperature was gradually raised to 240°C, the vacuum degree was gradually reduced to 30Pa, and the reaction was continued for 7.0h to obtain poly-bis-(5-carboxyfurfuryl) ether 1,4-cyclohexanedimethanol ester. The intrinsic viscosity and thermal stability of the obtained polyester were tested respectively. The intrinsic viscosity of the polyester was 0.81dL / g, the glass transition temperature was 63°C, and the thermal weight loss temperature (T d ,5%) is 392℃ and the elongation at break is 190±23%.
[0060] Example 12
[0061] Bis-(5-carboxyfurfuryl) ether and 1,4-cyclohexanedimethanol were added to the reactor in a molar ratio of 1:1.6, wherein the ratio of cis-trans isomers of 1,4-cyclohexanedimethanol was 4.0, and then 1‰ of dibutyltin oxide catalyst was added to the di-(5-carboxyfurfuryl) ether. Under the protection of high-purity nitrogen, the temperature was gradually raised to 190°C for esterification and the reaction was carried out for 6.0 hours. Then, 1.0‰ of antimony acetate, a polycondensation catalyst, and 1.0‰ of triphenyl phosphate, a stabilizer, were added to the di-(5-carboxyfurfuryl) ether. The temperature was gradually raised to 240°C, the vacuum degree was gradually reduced to 30Pa, and the reaction was carried out for 7.0 hours to obtain poly-bis-(5-carboxyfurfuryl) ether 1,4-cyclohexanedimethanol ester. The intrinsic viscosity and thermal stability of the obtained polyester were tested respectively. The intrinsic viscosity of the polyester was 0.83dL / g, the glass transition temperature was 51°C, and the thermal weight loss temperature (T d ,5%) is 388℃ and the elongation at break is 59±14%.
[0062] Embodiment 13
[0063] Bis-(5-carboxyfurfuryl) ether and 1,4-cyclohexanedimethanol were added to the reactor in a molar ratio of 1:1.6, wherein the ratio of cis-trans isomers of 1,4-cyclohexanedimethanol was 2.0, and then 1‰ of dibutyltin oxide catalyst was added to the di-(5-carboxyfurfuryl) ether. Under the protection of high-purity nitrogen, the temperature was gradually raised to 190°C for esterification and the reaction was carried out for 6.0 hours. Then, 1.0‰ of antimony acetate, a polycondensation catalyst, and 1.0‰ of triphenyl phosphate, a stabilizer, were added to the di-(5-carboxyfurfuryl) ether. The temperature was gradually raised to 240°C, the vacuum degree was gradually reduced to 30Pa, and the reaction was carried out for 7.0 hours to obtain poly-bis-(5-carboxyfurfuryl) ether 1,4-cyclohexanedimethanol ester. The intrinsic viscosity and thermal stability of the obtained polyester were tested respectively. The intrinsic viscosity of the polyester was 0.80dL / g, the glass transition temperature was 57°C, and the thermal weight loss temperature (T d ,5%) is 372℃ and the elongation at break is 94±13%.
[0064] Embodiment 14
[0065] 5,5'-(oxybis(methylene))bis(furan-2-carboxylic acid dimethyl ester) and ethylene glycol were added to the reactor in a molar ratio of 1:1.6, and then 1‰ of 5,5'-(oxybis(methylene))bis(furan-2-carboxylic acid dimethyl ester) was added as a catalyst dibutyltin oxide. Under the protection of high-purity nitrogen, the temperature was gradually raised to 160°C for esterification and the reaction was continued for 6.0 hours. Then 1.0‰ of 5,5'-(oxybis(methylene))bis(furan-2-carboxylic acid dimethyl ester) was added as a polycondensation catalyst antimony acetate and 1.0‰ of a stabilizer triphenyl phosphate. The temperature was gradually raised to 210°C, the vacuum degree was gradually reduced to 30Pa, and the reaction was continued for 7.0 hours to obtain polyester. The obtained polyester was tested for intrinsic viscosity, thermal stability, etc. The intrinsic viscosity of the polyester was 1.02dL / g, the glass transition temperature was 72°C, and the thermal weight loss temperature (T d ,5%) is 335℃ and the elongation at break is 220±25%.
[0066] Embodiment 15
[0067] 5,5'-(oxybis(methylene))bis(furan-2-carboxylic acid dimethyl ester), ethylene glycol and neopentyl glycol were added to the reactor in a molar ratio of 1:1.2:1, and then 1‰ of dibutyltin oxide catalyst was added to di-(5-carboxyfurfuryl) ether. Under the protection of high-purity nitrogen, the temperature was gradually raised to 160°C for esterification and the reaction was carried out for 6.0 hours. Then, 0.6‰ of di-(5-carboxyfurfuryl) ether was added as a polycondensation catalyst antimony acetate and 0.6‰ of monobutyl tin triisooctanoate, and 1.0‰ of triphenyl phosphate stabilizer were added. The temperature was gradually raised to 210°C, and the vacuum degree was gradually reduced to 30Pa. The reaction was carried out for 7.0 hours to obtain a copolyester. The intrinsic viscosity and thermal stability of the obtained copolyester were tested respectively. The intrinsic viscosity of the copolyester was 0.82dL / g, the glass transition temperature was 39°C, and the thermal weight loss temperature (T d ,5%) is 374℃ and the elongation at break is 240±19%.
[0068] Example 16
[0069] Bis-(5-carboxyfurfuryl) ether, ethylene glycol and pentacyclopentadecanediol were added to the reactor in a molar ratio of 1:1.8:0.6, and then a catalyst dibutyltin oxide with a molar amount of 1‰ of bis-(5-carboxyfurfuryl) ether was added. Under the protection of high-purity nitrogen, the temperature was gradually raised to 170°C for esterification and the reaction was carried out for 6.0 hours. Then, a polycondensation catalyst antimony acetate with a molar amount of 1.0‰ of bis-(5-carboxyfurfuryl) ether and 0.4‰ of stabilizers triphenyl phosphate and trimethyl phosphate were added, and the temperature was gradually raised to 220°C. The vacuum degree was gradually reduced to 30Pa, and the reaction was carried out for 7.0 hours to obtain a copolyester. The obtained copolyester was tested for characteristic viscosity, thermal stability, etc. The copolyester has a characteristic viscosity of 0.89dL / g, a glass transition temperature of 76°C, and a thermal weight loss temperature (T d ,5%) is 380℃ and the elongation at break is 310±36%.
[0070] Embodiment 17
[0071] Bis-(5-carboxyfurfuryl) ether, 1,4-butanediol, and 1,4-cyclohexanedimethanol were added to the reactor in a molar ratio of 1:1:0.8, wherein the ratio of the cis-trans isomers of 1,4-cyclohexanedimethanol was 0.5, and then a catalyst tetrabutyl titanate with a molar amount of 2‰ of bis-(5-carboxyfurfuryl) ether was added, and under the protection of high-purity nitrogen, the temperature was gradually raised to 150°C for esterification, and the reaction was carried out for 6.0 hours, and then a polycondensation catalyst antimony trioxide with a molar amount of 1.0‰ of bis-(5-carboxyfurfuryl) ether and a stabilizer triphenyl phosphate with a molar amount of 1.0‰ were added, and the temperature was gradually raised to 230°C, and the vacuum degree was gradually reduced to 30Pa, and the reaction was carried out for 5.0 hours to obtain polybis-(5-carboxyfurfuryl) ether butanediol cyclohexanedimethanol ester. The intrinsic viscosity of the copolyester was 0.71dL / g, the glass transition temperature was 57°C, and the thermal weight loss temperature (T d ,5%) is 392℃, and the elongation at break is 170±11%.
[0072] Embodiment 18
[0073] Add bis-(5-carboxyfurfuryl) ether, ethylene glycol and 1,4-butanediol into the reactor in a molar ratio of 1:1:2, then add bis-(5-carboxyfurfuryl) ether with a molar amount of 1‰ of catalyst isopropyl titanate and 1‰ of isopropyl titanate, and gradually heat to 240°C for esterification under the protection of high-purity nitrogen. React for 2.0 hours, then add bis-(5-carboxyfurfuryl) ether with a molar amount of 1.0‰ of polycondensation catalyst titanium dioxide, 1.0‰ of stabilizer phosphorous acid and 1.0‰ of hypophosphorous acid, gradually heat to 290°C, gradually reduce the vacuum degree to 30Pa, react for 1.5 hours, and obtain copolyester. The obtained copolyester was tested for intrinsic viscosity, thermal stability, etc. The intrinsic viscosity of the copolyester is 0.80dL / g, the glass transition temperature is 54°C, and the thermal weight loss temperature (T d,5%) is 347℃ and the elongation at break is 350±20%.
[0074] Embodiment 19
[0075] Add bis-(5-carboxyfurfuryl) ether, ethylene glycol and 1,3-cyclohexanedimethanol into the reactor in a molar ratio of 1:1:0.6, then add zinc acetate as a catalyst with a molar amount of 1‰ of bis-(5-carboxyfurfuryl) ether, and gradually heat to 150°C for esterification under the protection of high-purity nitrogen, and react for 8.0 hours, then add titanium dioxide as a polycondensation catalyst with a molar amount of 1.0‰ of bis-(5-carboxyfurfuryl) ether, 1.0‰ of pyrophosphoric acid as a stabilizer and 1.0‰ of ammonium phosphate, gradually heat to 170°C, gradually reduce the vacuum degree to 30Pa, and react for 7.0 hours to obtain a copolyester. The obtained copolyester was tested for intrinsic viscosity, thermal stability, etc. The intrinsic viscosity of the polyester is 0.67dL / g, the glass transition temperature is 68°C, and the thermal weight loss temperature (T d ,5%) is 339℃ and the elongation at break is 120±14%.
[0076] Comparative Example 1
[0077] 2,5-furandicarboxylic acid and ethylene glycol were added to the reactor in a molar ratio of 1:1, and then 1‰ of 2,5-furandicarboxylic acid was added as a catalyst dibutyltin oxide. Under the protection of high-purity nitrogen, the temperature was gradually raised to 180°C for esterification and the reaction was continued for 5.0h. Then 1.0‰ of 2,5-furandicarboxylic acid was added as a polycondensation catalyst tetrabutyl titanate and 1.0‰ of a stabilizer triphenyl phosphate. The temperature was gradually raised to 220°C, and the vacuum degree was gradually reduced to 30Pa. The reaction was continued for 7.0h to obtain polyethylene 2,5-furandicarboxylate. The intrinsic viscosity and thermal stability of the obtained polyester were tested. The intrinsic viscosity of the polyester was 0.73dL / g, the glass transition temperature was 87°C, and the thermal weight loss temperature (T d ,5%) is 413℃ and the elongation at break is 5±2%.
[0078] It can be seen from the above embodiments and comparative example 1 that the polyester obtained by reacting bis-(5-carboxyfurfuryl) ether or its esterified product as a monomer with the above diol has a much higher elongation at break than the polyester in comparative example 1 while ensuring heat resistance. It can be seen that the polyester disclosed in the present application greatly improves the toughness of the polyester.
[0079] The embodiments described above are only some embodiments of the present invention, not all embodiments. In this application, the diols in the embodiments can be mixed with one or more of ethylene glycol, butanediol, hexanediol, neopentyl glycol, 1,4-cyclohexanedimethanol (cis-trans ratio is 0.25-4.0), 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, tricyclodecane dimethanol, dicyclopentanediol, 1,5-dimethyldicyclopentanediol, and pentacyclopentadecanediol. All other embodiments obtained by ordinary technicians in this field without creative work based only on the above diols are within the scope of protection of the present invention.
[0080] In the present application, the esterification or transesterification catalyst is a mixture of one or more of zinc acetate, tetrabutyl titanate, isopropyl titanate, titanium dioxide, dibutyltin oxide, stannous isooctanoate, and monobutyltin triisooctanoate. All other embodiments obtained by a person skilled in the art without creative work based only on the above-mentioned esterification or transesterification catalysts are within the scope of protection of the present invention.
[0081] In the present application, the polycondensation catalyst is mixed with one or more of antimony trioxide, antimony acetate, titanium dioxide, dibutyltin oxide, stannous isooctanoate, monobutyltin triisooctanoate, and germanium dioxide. All other embodiments obtained by ordinary technicians in the field without creative work based only on the mixed use of the above polycondensation catalysts belong to the scope of protection of the present invention.
[0082] In the present application, the stabilizer is a mixture of one or more of phosphorous acid, hypophosphorous acid, pyrophosphoric acid, ammonium phosphate, trimethyl phosphate, dimethyl phosphate, triphenyl phosphate, diphenyl phosphate, triphenyl phosphite, diphenyl phosphite, ammonium phosphite, and diammonium phosphate. All other embodiments obtained by ordinary technicians in the field without creative work based only on the above stabilizers are within the scope of protection of the present invention.
[0083] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for preparing polyester, characterized in that: The product is prepared by melt polycondensation of bis-(5-carboxyfurfuryl) ether or its ester as a monomer and diol.
2. The preparation method according to claim 1, characterized in that: The invention adopts bis-(5-carboxyfurfuryl) ether or its esterified product as monomer, and is obtained by melt polycondensation with diol in the presence of esterification or transesterification catalyst, polycondensation catalyst and stabilizer.
3. The preparation method according to claim 2, characterized in that: Bis-(5-carboxyfurfuryl) ether or its esterification product is used as a monomer, and reacted with a diol in the presence of an esterification or transesterification catalyst to obtain an intermediate product, and then the intermediate product is reacted with the polycondensation catalyst and the stabilizer to obtain the intermediate product.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The molar ratio of the bis-(5-carboxyfurfuryl) ether or its ester to the diol is 1:(1.2-3.0).
5. The preparation method according to claim 2 or 3, characterized in that: The molar ratio of the esterification or transesterification catalyst to the bis-(5-carboxyfurfuryl) ether or its esterification product is (0.3-3.0):1000.
6. The preparation method according to claim 2 or 3, characterized in that: The molar ratio of the polycondensation catalyst to the bis-(5-carboxyfurfuryl) ether or its ester is (0.3-3.0):1000.
7. The preparation method according to claim 2 or 3, characterized in that: The molar ratio of the stabilizer to the bis-(5-carboxyfurfuryl) ether or its ester is (0.4-3.0):1000.
8. The preparation method according to claim 3, wherein bis-(5-carboxyfurfuryl) ether or its esterified product is used as a monomer, and in the presence of an esterification or transesterification catalyst, reacted with a diol at 150 to 240° C. for 2.0 to 8.0 hours to obtain an intermediate product, and the intermediate product is reacted with the polycondensation catalyst and the stabilizer at 170 to 290° C. and a vacuum degree of ≤200 Pa for 1.5 to 10 hours to obtain a polyester.
9. The preparation method according to any one of claims 1 to 3, characterized in that: The diol is selected from one or more of ethylene glycol, butanediol, hexanediol, neopentyl glycol, a cis-trans ratio mixture of cyclohexanedimethanol, tricyclodecane dimethanol, dicyclopentanediol, 1,5-dimethyldicyclopentanediol, and pentacyclopentadecanediol; Preferably, the cyclohexanedimethanol is selected from one or more of 1,4-cyclohexanedimethanol cis-trans mixture, 1,2-cyclohexanedimethanol, and 1,3-cyclohexanedimethanol; Preferably, the cis-trans ratio of the 1,4-cyclohexanedimethanol cis-trans mixture is 0.25-4.
0.
10. The preparation method according to claim 2 or 3, characterized in that: The esterification or transesterification catalyst is selected from one or more of zinc acetate, tetrabutyl titanate, isopropyl titanate, titanium dioxide, dibutyltin oxide, stannous isooctanoate, and monobutyltin triisooctanoate; Preferably, the polycondensation catalyst is selected from one or more of antimony trioxide, antimony acetate, titanium dioxide, dibutyltin oxide, stannous isooctanoate, monobutyltin triisooctanoate, and germanium dioxide; Preferably, the stabilizer is a phosphorus stabilizer; Preferably, the phosphorus stabilizer is selected from one or more of phosphorous acid, hypophosphorous acid, pyrophosphoric acid, ammonium phosphate, trimethyl phosphate, dimethyl phosphate, triphenyl phosphate, diphenyl phosphate, triphenyl phosphite, diphenyl phosphite, ammonium phosphite, and diammonium dihydrogen phosphate.